Occupational Stress among Academicians between Two Selected Universities in Malaysia and Indonesia During the COVID-19 Pandemic: A Comparative Study - Rusli, Nur Husna; Anua, Siti Marwanis; Endarti, Ajeng Tias; Wan Mohd Amin, Wan Siti Hajar; Mazlan, Nurzafirah; E Ibrahim, Tengku Azmina (UI Scholars Hub, 2023)
Occupational stress has become a major concern for both employees and employers globally. Stress leads to a loss of interest among workers as well as unproductive and valueless outputs if not managed well. The education sector is one work setting dominated by stress. This comparative cross-sectional study aimed to determine the levels of depression, anxiety, and stress among academicians as well as their work-related stressors and coping strategies between a selected public university in Malaysia and a private university in Indonesia. A total of 82 academicians from universities in Malaysia and 52 from Indonesia were recruited using convenience sampling. Data was collected using a validated self-reported questionnaire via Google Forms. The prevalence of depression, anxiety, and stress among Malaysian academicians was 19.5%, 29.5%, and 12.2%, respectively. In contrast, the prevalence of depression, anxiety, and stress among Indonesian academicians was 15.7%, 33.3%, and 9.8%. Career development, research, teaching, and interpersonal relationships significantly contributed to stress at both universities (p-value<0.05). Participants from both universities reported using active coping, planning, venting, self-distraction, positive reframing, acceptance, and religion as coping strategies. In conclusion, determining depression, anxiety, and stress prevalence; major work-related stressors; and coping strategies are essential to maintaining the safety, health, and well-being of academicians, which eventually can encourage university administrators to provide support in enhancing their quality of life.